The synthesis of Ru/CNF colloidal catalysts: Comparison of ex-situ and in-situ methods. (2017) - Demidova, Yuliya S.; Simakova, Irina L.; Schubert, Tim; Yu. Murzin, Dmitry
Abstract: Carbon nanofibers supported Ru catalysts (Ru/CNF) were synthesized by the colloidal method, varying the immobilization procedure (i.e. ex-situ or in-situ method of Ru catalyst synthesis), and the reducing agent nature. Hydrothermal stability of the synthesized Ru catalysts was studied aiming on further application of these catalysts in aqueous phase transformations. The in-situ procedure of Ru catalyst synthesis was shown to give a higher Ru nanoparticles dispersion, while the ex-situ method provided a better size control and resistance to leaching under hydrothermal conditions as well as during the catalysts synthesis.